ANTIHYPERGLYCEMIC ACTIVITY OF JAMBU MAWAR LEAVES EXTRACT (Syzygium jambos (L.) Aston) ON MALE RABBIT ALLOXANT INDUCTED - Prastiwi, Mela; Kartika, Rudi; Hindryawati, Noor (Jurusan Kimia FMIPA UNMUL, 2019)
Antihyperglycemic activity of jambu mawar leaves extract (Syzygium jambos (L.) Aston) to lower blood glucose levels in male rabbits (Oryctolagus cuniculus) induced by alloxant has been conducted. Simplicia jambu mawar leaves (Syzygium jambos (L.) Aston) were macerated using ethanol 96%. The testing activity of antihyperglycemic done experimentally et the laboratory with each dose of 374.5 mg/Kg and 749 mg/Kg given orally on the male rabbits in the induction alloxant. Measurement of blood glucose levels was done on the (7, 14, 21, 28 and 32) by using a glucometer and glucose test strips. The ethanol extracts of jambu mawar leaves (Syzygium jambos (L.) Aston) revealed the effect by decreasely the blood glucose levels in male rabbits induced by alloxant. Keywords: Jambu Mawar leaves (Syzygium jambos (L.) Aston), Antihyperglicemic, Alloxant and glucometer.